A chiral thiourea and a phosphazene for fast and stereoselective organocatalytic ring-opening-polymerization of racemic lactide. Issue 31 (18th March 2021) - Zaky, Mohamed Samir; Wirotius, Anne-Laure; Coulembier, Olivier; Guichard, Gilles; Taton, Daniel
Abstract : The isoselective organocatalyzed ring-opening polymerization of rac -lactide is triggered by a chiral binary organocatalytic system, achieving highly semi-crystalline and metal-free polylactides. Abstract : Control of stereoregularity is inherent to precision polymerization chemistry for the development of functional materials. A prototypal example of this strategy is the ring-opening polymerization (ROP) of racemic lactide ( rac -LA), a bio-sourced monomer. Despite significant advances in organocatalysis, stereoselective ROP of rac -LA employing chiral organocatalysts remains unexplored. Here we tackle that challenge by resorting to Takemoto's catalyst, a chiral aminothiourea, in the presence of a phosphazene base. This chiral binary organocatalytic system allows for fast, chemo- and stereoselective ROP of rac -LA at room temperature, yielding highly isotactic, semi-crystalline and metal-free polylactide, with a melting temperature as high as 187 °C.